2018
DOI: 10.3389/fped.2018.00383
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype Profiling and Allergy in Otitis-Prone Children

Abstract: Background: Otitis-prone children can present some distinctive clinical patterns and although a number of known risk factors for recurrent acute otitis media (RAOM) are known, no dedicated epidemiological models have been developed to explain clinical heterogeneity.Methods: A preliminary retrospective pilot study was planned to evaluate the possible effect of allergic disease in the development of different disease phenotypes in otitis-prone children aged 3–10 years, particularly the absence (simple RAOM), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 41 publications
0
19
0
2
Order By: Relevance
“…Most relevant clinical articles 38,39,39,40,40,41,41,42,42,44‐47 included in the qualitative analyses, investigating specifically association between OME and allergy, are summarized in Table 3. The majority of articles included are of good quality and support a link between OME and allergy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most relevant clinical articles 38,39,39,40,40,41,41,42,42,44‐47 included in the qualitative analyses, investigating specifically association between OME and allergy, are summarized in Table 3. The majority of articles included are of good quality and support a link between OME and allergy.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Torretta et al 44 demonstrated that allergy or atopy was significantly higher in otitis‐prone children with OME than in those with simple RAOM: Atopy was found in 73% of the children with both RAOM and OME versus 39.5% of those with simple RAOM, while allergy was found in 60% and 36%, respectively. The authors 44 suggested that children with both RAOM and OME are clinically different from children with simple RAOM, as they have a more complex clinical presentation that may be sustained by underlying allergy or atopy. Interestingly, in the same manuscript, children with both RAOM and OME were more frequently affected by adenoid hypertrophy (AH) ( P = 0.016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study [10] revealed higher prevalence of atopy or allergy in children with a recurrent presence of episodes of OME between acute infections (atopy: 73.0% vs. 39.5%, p < 0.001; allergy: 60.0% vs. 36.1%, p = 0.049), which may suggest that children with recurrent acute otitis media (AOM) with OME are clinically different from children with simple recurrent AOM, because they have a more complex clinical presentation that includes not only adenoidal disease and audiological impairment, but also an underlying allergy or atopy.…”
Section: The Role Of Allergy In Otitis Media With Effusionmentioning
confidence: 98%